Strategi Ketercapaian Smart Environment di SWK Gedebage - Rajwa Komalaningtyas; Tarlani Tarlani (UNISBA Press, 2022)
Abstract. With the increasing number of urban problems, the government, in this case as a policy maker, can make policy innovations, which one to use technology. Through the Movement Towards 100 Smart City program created by the Ministry of Information and Technology, Bandung has become one of these cities. SWK Gedebage, which is one of eight SWKs in Bandung that will become the City Service Center (PPK) and a technopolis area or area built based on technology, which is stipulated in the Bandung City RDTR 2015-2035. The main problem in Gedebage SWK is flooding, there is garbage piling up in the Gedebage Main Market which causes clogged drainage, causing flooding on roads, to flooding in settlements and housing. Therefore, this study aims to determine the potential and environmental problems in SWK Gedebage and make an achievement strategy based on smart environment criteria in realizing SWK Gedebage as a Technopolis Area and PPK Gedebage. The analysis used using SWOT with secondary data collection of government documents and primary field findings. The strategy is made in accordance with the criteria contained in the smart environment, Environmental Protection Program (Protection), Waste and Waste Management (Waste), and Responsible Energy Management (energy). The results of the SWOT found that the strategic position was made with the problem of flooding and waste, through improving the management of flood management on the Cinambo River border and improving the management of household waste disposal using technology (Incinerator, recycling, and composting). Abstrak. Semakin banyaknya permasalah perkotaan maka pemerintah yang dalam hal ini sebagai pembuat kebijakan dapat melakukan inovasi kebijakan, salah satunya dengan penggunaan teknologi. Melalui program Gerakan Menuju 100 Smart city yang dibuat oleh Kementrian dan Informasi, Kota Bandung menjadi salah satu kota tersebut. SWK Gedebage yang merupakan satu dari delapan SWK di Kota Bandung yang akan menjadi Pusat Pelayanan Kota (PPK) dan merupakan kawasan teknopolis atau kawasan yang dibangun berbasis teknologi, yang ditetapkan pada RDTR Kota Bandung 2015-2035. Permasalahan utama di SWK Gedebage adalah banjir, terdapat sampah menumpuk di Pasar Induk Gedebage yang menyebabkan drainase tersumbat sehingga menimbulkan banjir di ruas jalan, sampai dengan banjir di permukiman dan perumahan. Maka dari itu, penelitian ini bertujuan untuk mengetahui potensi dan permasalah lingkungan di SWK Gedebage dan membuat strategi ketercapaian berdasarkan kriteria smart environment dalam mewujudkan SWK Gedebage sebagai Kawasan Teknopolis dan PPK Gedebage. Analisis yang digunakan menggunakan SWOT dengan pengumpulan data sekunder dokumen pemerintah dan primer penemuan lapangan. Strategi yang dibuat sesuai dengan kriteria yang terdapat di smart environment, Program Proteksi Lingkungan (Protection), Tata Kelola Sampah dan Limbah (Waste), dan Tata Kelola Energi yang bertanggung jawab (energy). Hasil dari SWOT ditemukan bahwa posisi strategi dibuat dengan permasalahan banjir dan sampah, melalui peningkatan pengelolaan penanganan banjir di sempadan Sungai Cinambo dan peningkatan pengelolaan pembuangan limbah rumah tangga menggunakan teknologi (Incenerator, recycling, dan composting).